Investigation of the Hydrodynamics of Fixed Bed Reactor: Co-current Upflow - Rashid, Syamsina (Universiti Teknologi Petronas, 2005)
Themain objective of this projectis to investigate the hydrodynamic characteristics of co-current upflow of gas and liquid in a fixed bed reactor. This is an experimental based project utilizing the packed bed reactor for residence time distribution (RTD) studies. In this project, the RTD of a bench-scale multiphase was studied using air as a gaseous phase andwater as a liquid phase. The ranges of air and water velocities are kept at such levels as to simulate the hydrogen/oil ratios of typical bench-scale hydroprocessing units. Theexperiments are conducted in upflow mode of operation in the reactor, with increasing gas/liquid ratio. The effects of gas and liquid velocities on different hydrodynamic parameters such as pressure drop and operating liquidholdup are investigated. Operating the fixed bed reactor in upflow mode showed increase in pressure drop, and decrease in operating liquid holdup. Three moments analysis, which are mean residence time, variance, and skewness, are evaluated in order to characterize the RTD. These three moments analysis revealed an increase in mean residence time, and also increases in variance and skewness with increasing gas/liquid ratio. Other parameters such as bed Pecletnumber of liquidand stagnant zonevolume were also investigated with variation of gas and liquid velocities as to measure the efficiency of the reactor. Decreasing Peclet number and stagnant zone volume suggested the decreasing efficiency of the reactor, with increasing gas/liquid ratio. The discrepancies in experimental results suggested that there are conditions to be altered in order to eliminate the inconsistency.